1980
DOI: 10.2323/jgam.26.119
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on an asporogenous mutant of Bacillus subtilis lacking in vivo proteolytic activity.

Abstract: We previously isolated an early-blocked asporogenous mutant of Bacillus subtilis Marburg, strain 61, (1) and we speculated that spore-type RNA polymerase did not function but that the vegetative RNA polymerase was active in this mutant from the measurement of protein and RNA synthesis of the mutant in both logarithmic and stationary phases (1, 2). We also found that the degradation of preformed proteins occurred in the parent strain during the stationary phase, while no significant degradation was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Genetic and physiological evidence has been presented for a role of ISP-1 in bulk protein degradation during sporulation (15,27), and evidence has been reported that mutations affecting ISP-2 (12, 32) also result in impaired ability of cells to degrade intracellular proteins during sporulation. In most previous studies (21, 29), workers have attempted to correlate intracellular proteinase activity and protein degradation in cells sporulating in complex or semidefined media.…”
mentioning
confidence: 99%
“…Genetic and physiological evidence has been presented for a role of ISP-1 in bulk protein degradation during sporulation (15,27), and evidence has been reported that mutations affecting ISP-2 (12, 32) also result in impaired ability of cells to degrade intracellular proteins during sporulation. In most previous studies (21, 29), workers have attempted to correlate intracellular proteinase activity and protein degradation in cells sporulating in complex or semidefined media.…”
mentioning
confidence: 99%
“…4). Evidently, calcium ions must be present in the growth medium in order to produce normal synthesis and/or activation of ISP-1, which accounts for about 80% of the total proteinase activity in the soluble fraction (5,29). The data in Table 2 confirm that in Ca2"-containing CDSM medium, ISP-1 accounted for about 74% of the total azocaseinase activity in the cells at t1o.…”
Section: Effect Of L-leucine Concentrations On Protein Degradationmentioning
confidence: 63%
“…The results of these experiments are summarized in Table TABLE 1 (29,36), we studied the effect of Ca2" on sporulation, proteinase activity, and proteolysis in B. subtilis cells. In CDSM, cells were strongly dependent on the addition of calcium ions to the medium to achieve maximal sporulation ( Table 2).…”
Section: Effect Of L-leucine Concentrations On Protein Degradationmentioning
confidence: 99%
“…These data indicate that ISP-1 is synthesized beginning at to but is not enzymatically active until t4. The mechanism for maintaining ISP-1 in the inactive form or the nature of the inactive protein is unknown, although several forms of regulation have been proposed (12,13,19). A zymogen-like precursor of another intracellular protease, the small-acid-solubleprotein-degrading enzyme, has been observed in sporulating cells (7).…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of this enzyme in sporulation has not been established, and little is known about the regulation of ISP-1 expression and control of protease activity. It has been suggested that ISP-1 activity might be regulated by interaction with a proteinaceous inhibitor, calcium availability, or activation by membrane-bound proteases (12,13,19). A recent report presented immunological evidence that ISP-1 was initially synthesized as an enzymatically inactive protein that was subsequently converted to an active protease (3).…”
mentioning
confidence: 99%